2016
DOI: 10.5430/jst.v6n2p43
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cold therapy on the incidence and severity of paclitaxel induced peripheral neuropathy: A pilot study

Abstract: Background: Peripheral neuropathy is a common side effect induced by chemotherapy agents like Cisplatin, Paclitaxel and Docetaxel. At present, there is no preventive strategy available against the development of neuropathy. This pilot study was performed to evaluate the feasibility of cold therapy and its impact on the incidence and severity of neuropathy induced by paclitaxel in a dose dense adjuvant regimen among patients with breast cancer. Methods: All adult female patients with early breast cancer planned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
(14 reference statements)
1
4
0
Order By: Relevance
“…The results of this study suggest that continuous-flow limb hypothermia can preserve specific parameters of nerve conduction and significantly benefit some patients undergoing paclitaxel chemotherapy. These results are supported by another pilot study providing evidence that limb hypothermia has a potential to alleviate paclitaxel-induced symptoms of peripheral neuropathy in breast cancer patients (Younus et al, 2016 ). Kim et al demonstrated that systemic administration of a reactive oxygen species scavenger, tempol, which has previously been shown to be of benefit in a rat model of cancer-induced bone pain (Zhou et al, 2018 ), also ameliorated and prevented neuropathic pain induced by paclitaxel in rats.…”
Section: Introductionsupporting
confidence: 56%
“…The results of this study suggest that continuous-flow limb hypothermia can preserve specific parameters of nerve conduction and significantly benefit some patients undergoing paclitaxel chemotherapy. These results are supported by another pilot study providing evidence that limb hypothermia has a potential to alleviate paclitaxel-induced symptoms of peripheral neuropathy in breast cancer patients (Younus et al, 2016 ). Kim et al demonstrated that systemic administration of a reactive oxygen species scavenger, tempol, which has previously been shown to be of benefit in a rat model of cancer-induced bone pain (Zhou et al, 2018 ), also ameliorated and prevented neuropathic pain induced by paclitaxel in rats.…”
Section: Introductionsupporting
confidence: 56%
“…Several studies have employed frozen gloves as a mode of cryotherapy in preventing CIPN [4,8,9,14,23,29,31,32]. These studies have demonstrated frozen gloves are able to deliver considerable regional hypothermia, however, this effect is not sustained or stable thereby potentially reducing the efficacy of vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent trial reported by Hanai et al (2018), cryotherapy in the form of frozen gloves was effective in preventing and reducing the occurrence of CIPN [9]. Similarly, inspired by scalp cooling therapy to combat chemotherapy-induced alopecia (CIA) [7,15], several groups have demonstrated promising results that the use of frozen gloves and socks concomitantly with the chemotherapy infusion is efficacious in reducing CIPN [4,9,23,29,31,32]. However, latest reports indicate that the frozen gloves have been recalled due to incidences of frostbite and other patient safety issues [10].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of rehabilitative methods, such as exercise and cold application, have been tested with positive effects in reducing the impact of CIPN symptoms and in improving the life quality of the patient. [ 18 19 20 21 22 23 ] Literature suggests that a well-planned exercise program produces safe and effective results. [ 19 21 23 ] Here, the type and frequency of the exercise is an important determinant.…”
Section: Introductionmentioning
confidence: 99%
“…The cold application was reported to reduce the severity of neuropathy in previous studies. [ 20 25 26 ] Hanai et al . [ 26 ] indicated that the occurrences of paclitaxel-induced peripheral neuropathy were less frequent in the patients who used frozen gloves and socks.…”
Section: Introductionmentioning
confidence: 99%